The Above-Ground Part of Submerged Macrophytes Plays an Important Role in Ammonium Utilization - Xian, Ling; Ochieng, Wyckliffe Ayoma; Muthui, Samuel Wamburu; Otieno, Duncan Ochieng; Yu, Siwei; Li, Wei; Yan, Xue; Yu, Quan; Liu, Fan (Frontiers in Plant Science, 2022)
As a paradoxical nutrient in water ecosystems, ammonium can promote plants growth under moderate concentration, but excess of it causes phytotoxic effects. Previous research has revealed that glutamate dehydrogenase in the above-ground part of submerged macrophytes plays an important role in ammonium detoxification. However, the strategies of ammonium utilization at the whole plant level of submerged macrophytes are still unclear and the role of above-ground part in nutrient utilization has not been clearly elucidated in previous studies, hence, directly influencing the application of previous theory to practice. In the present research, we combined the methods of isotopic labeling and enzymes estimation to investigate strategies of ammonium utilization by submerged macrophytes. The results showed that when [NH4+-N] was 50 mg L-1, 15N taken up through the above-ground parts was 13.24 and 17.52 mg g-1 DW, while that of the below-ground parts was 4.24 and 8.54 mg g-1 DW in Potamogeton lucens and Myriophyllm spicatum respectively. The ratios of 15N acropetal translocation to uptake were 25.75 % and 35.69 %, while those of basipetal translocation to uptake were 1.93 % and 4.09 % in P. lucens and M. spicatum respectively. Our results indicated that the above-ground part was not only the main part for ammonium uptake, but also the major pool of exogenous ammonium. Besides, the dose-response curve of GDH (increased by 20.9 % and 50.2 % under 15 and 50 mg L-1 [NH4+-N] respectively) exhibited by the above-ground parts of M. spicatum indicates that it is the main site for ammonium assimilation of tolerant species. Our present study identifies ammonium utilization strategy of submerged macrophytes and reveals the important role of the above-ground part in nutrient utilization providing a new insight on the researches of nutrient utilization by plants and theoretical supports for water restoration by phytoremediation.